Natural durability of timber species exposed to xylophagous fungi in southern Durango, Mexico - Ontiveros-Moreno,Yolanda; Colín-Urieta,Serafín; Corral-Rivas,José Javier; Hernández-Díaz,José Ciro; Prieto-Ruíz,José Ángel; Carrillo-Parra,Artemio (PeerJ, 2023)
Introduction Wood is a natural resource used for construction and the manufacture of many products. This material is exposed to damage due to biotic and abiotic factors. An important biotic factor is wood-degrading fungi that generate large economic losses. The objectives of this study were to determine the effect of xylophagous fungi (Coniophora puteana and Trametes versicolor) on the natural durability of six timber species in southern Durango, Mexico, and to establish differences between fungal effects on each tree species. Materials and Methods Samples of Pinus durangensis, P. cooperi, P. strobiformis, Juniperus deppeana, Quercus sideroxyla, and Alnus acuminata were exposed to fungi for 4 months under laboratory conditions according to European Standard EN350-1. Samples of Fagus sylvatica were used as control. Durability was determined as the percentage of wood mass loss for each species. Welch ANOVA tests were performed to establish differences among tree species. Welch t-tests were used to prove loss mass differences between fungi for each tree species. Results The most resistant species to C. puteana were P. durangensis, J. deppeana, P. cooperi and P. strobiformis, showing mean mass losses lower than 8.08%. The most resistant species to T. versicolor were J. deppeana, P. strobiformis and P. durangensis (mean mass losses lower than 7.39%). Pinus strobiformis and Q. sideroxyla were more susceptible to C. puteana effect; in contrast, P. durangensis and P. cooperi showed more damage due to T. versicolor degradation. Conclusions Woods of P. durangensis, P. cooperi, P. strobiformis and Juniperus deppeana are well adapted to infection by these xylophagous fungi and are therefore highly recommended for commercial use in southern Durango, Mexico.
Keywords: Coniophora puteana; Trametes versicolor; Pinus spp; Juniperus deppeana; Natural durability; Xylophagus fungi